Nature versus nurture: distinguishing effects from stellar processing and chemical evolution on carbon and nitrogen in red giant stars - Roberts, John; Pinsonneault, Marc H; Johnson, Jennifer A; Zinn, Joel C; Weinberg, David H; Vrard, Mathieu; Tayar, Jamie; Stello, Dennis; Mosser, Benoît; Johnson, James W; Cao, Kaili; Stassun, Keivan G; et al. (Monthly notices of the Royal Astronomical Society, 2024)
The surface [C/N] ratios of evolved giants are strongly affected by the first dredge-up (FDU) of nuclear-processed material from stellar cores. C and N also have distinct nucleosynthetic origins and serve as diagnostics of mixing and mass-loss. We use subgiants to find strong trends in the birth [C/N] with [Fe/H], which differ between the low-α and high-α populations. We demonstrate that these birth trends have a strong impact on the surface abundances after the FDU. This effect is neglected in current stellar models, which use solar-scaled C and N. We map out the FDU as a function of evolutionary state, mass, and composition using a large and precisely measured asteroseismic data set in first-ascent red giant branch (RGB) and core He-burning, or red clump (RC), stars. We describe the domains where [C/N] is a useful mass diagnostic and find that the RC complements the RGB and extends the range of validity to higher mass. We find evidence for extra mixing on the RGB below [Fe/H] = −0.4, matching literature results, for high-α giants, but there is no clear evidence of mixing in the low-α giants. The predicted signal of mass-loss is weak and difficult to detect in our sample. We discuss implications for stellar physics and stellar population applications.